Przegląd ostatnich prac włoskich w dziedzinie nośności granicznej - GIANGRECO, Elio (Engineering Transactions, 1966)
Recent Italian contributions in the limit designA complete description of progress reached by the scientific researches made in Italy during the last few years in the field of limit design should be connected with the Italian studies already performed as well as the scientific contributions of foreign countries, which certainly affected the course of Italian theoretical and experimental researches. We naturally must consider all these elements as already acquired and we must confine ourselves to a very general panoramic review of Italian contributions, signalling those researches which, because of their original set up and easy application, seem worth to be pointed out. In Italy, as well as in foreign countries, two main aspects can be seen in the studies performed: the progressive method, which follows the phenomenon gradual evolution up to the collapse, holding in account the plastic adaptation and the elastic recovery, and the limit design which refers only to the last event of the structure characterizing the collapse condition through the collapse kinematic mechanism. Some attempts were made to trace an intermediate way between these two methods; the method strictly adherent to the physical reality of the phenomenon but full of complications, and the very simple one, but too schematic of the plastic hinges. Therefore, our illustration fundamentally shall go on within these consideration.